Investigating Islamic Financial Market: a Study in Jakarta Islamic Index - Asri Jaya; Nurlina (Yayasan Rumah Peneleh, 2022)
This study aims to determine the effect of the current ratio (CR), debt-to-equity ratio (DER), return on equity (ROE), and earnings per share (EPS) on the stock prices of companies listed on the Jakarta Islamic Index (JII) for the 2016-2016 period. 2020. By employing a descriptive quantitative approach, and secondary data collected, a multiple linear regression analysis was conducted. The results of the study found that: the current ratio (CR) has a positive and significant effect on the stock prices of companies listed in JII, the debt-to-equity ratio (DER) has no effect on the stock prices of companies listed on JII. Meanwhile, ROE has a positive and significant effect on the stock price of companies listed on JII and EPS has a positive and significant effect on the stock prices of companies listed on JII.